P08.05 Lentiviral protein Vpx delivery systems as potential weapons to improve cytarabine treatment response against acute myeloid leukemia. (21st September 2022) - Nair, R; Sponheimer, M; Salinas-Illarena, A; Côrte-Real, JV; Subklewe, M; Baldauf, HM
Abstract : Background: The effective treatment of the blood cancer type acute myeloid leukemia (AML) presents several challenges. One of them is resistance to Cytarabine (ara-C), which is the primary chemotherapeutic drug used as front-line treatment against AML. In 2017, it was reported that sterile alpha motif and HD-domain-containing protein 1 (SAMHD1) plays a role in ara-C resistance. 1 SAMHD1 is an enzyme that reduces the level of dNTPs in cells, thereby serving as an attractive target for AML treatment. 1 The lentiviral accessory protein Vpx, found in Simian Immunodeficiency Viruses (SIV) and Human Immunodeficiency Virus-2 (HIV-2), is known to target SAMHD1 for proteasomal degradation. 2 Hence, we aim to use Vpx to reduce SAMHD1 levels in AML cells to improve ara-C sensitivity. Methods: In order to manipulate SAMDH1 levels using Vpx, different Vpx delivery systems were developed. These were virus-like particles (VLPs) packaged with different homologs of Vpx from SIV and HIV-2, and cell-penetrating peptides (CPPs) bound to either a 67 amino acid truncated SIVmac Vpx (67aaVpx) or to the WT full-length form. Two different CPPs were used in the synthesis: TAT and CPP44, the latter is based on a study by Kondo et al.. 3 Results: Upon treating different AML cell lines with the VLPs, we observed different SAMHD1-degradation capacities of the different Vpx homologs. Vpx from SIV isolated from macaques (mac239 and mac251) performed the best, compared to Vpx from other lineages. They also increased the ara-C sensitivity of THP-1 cells, which is an AML cell line with high SAMHD1 expression levels, up to 45-fold. Vpx from HIV-2 7312a only partially increased ara-C sensitivity, while HIV-2 Rod9 Vpx did not show any SAMHD1 degradation or improvement in ara-C sensitivity despite its high packaging efficiency in the VLPs. As for the CPPs, CPP44 bound to 67aaVpx showed better uptake and SAMHD1 degradation compared to the TAT bound 67aaVpx in THP-1 cells. Upon co-treatment with ara-C, up to a 5-fold reduction in IC50 was observed when treated with CPP44-bound 67aaVpx. In an attempt to increase efficiency, full-length Vpx-bound CPPs will be prepared, and trials using these CPPs are currently underway. Conclusion: We demonstrate that inducing SAMHD1 degradation by Vpx delivered via VLPs or CPPs efficiently improved ara-C sensitivity in AML cell lines. Since the VLPs presented a better efficiency compared to the CPPs, we are currently testing their efficiency in primary AML blasts, ex vivo . Ultimately, combining a Vpx delivery system with treatments containing ara-C could improve treatment outcomes in high-SAMHD1 patients who fail to respond effectively to ara-C treatment. References: Schneider C, Oellerich T, Baldauf HM, et al . SAMHD1 is a biomarker for cytarabine response and a therapeutic target in acute myeloid leukemia. Nat Med 2017 Feb 1;23 (2):250–5. Ahn J, Hao C, Yan J, et al . HIV/Simian Immunodeficiency Virus (SIV) Accessory Virulence Factor Vpx Loads the Host Cell Restriction Factor SAMHD1 onto the E3 Ubiquitin Ligase Complex CRL4 DCAF1. 2012;287 (15):12550–8. Kondo E, Saito K, Tashiro Y, et al . Tumour lineage-homing cell-penetrating peptides as anticancer molecular delivery systems. Nat Commun 2012 Jan 17;3 (1):951. Disclosure Information: R. Nair: None. M. Sponheimer: None. A. Salinas-Illarena: None. J.V. Côrte-Real: None. M. Subklewe: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; German Research Foundation, SFB-TRR, Bavarian Elite Graduate Training Network, Wilhelm-Sander Stiftung, Else-Kröner-Fresenius Stiftung, Bavarian Center for Cancer Research. C. Other Research Support (supplies, equipment, receipt of drugs or other in-kind support); Significant; AMGEN, BMS, Janssen, Kite/Gilead, Miltenyi, MorphoSys, Novartis, Roche, Seattle Genetics. D. Speakers Bureau/Honoraria (speakers bureau, symposia, and expert witness); Significant; AMGEN, BMS, Janssen, Kite/Gilead, Roche, Novartis, Pfizer, Celgene, Takeda. F. Consultant/Advisory Board; Significant; Novartis, Janssen, AMGEN, Celgene, Kite/Gilead, Takeda. H.M. Baldauf: B. Research Grant (principal investigator, collaborator or consultant and pending grants as well as grants already received); Significant; Wilhelm-Sander-Stiftung, Friedrich-Bauer-Stiftung.